PENCEGAHAN STUNTING MELALUI INOVASI AUDIO AFIRMASI POSITIF ASI EKSLUSIF BERBASIS TRI KAYA PARISUDHA - Kadek Agustina Puspa Ningrum; Ni Luh Linda Ayuni Tania (LPPM Universitas Abdurrab, 2026)
Background: Stunting is a significant health issue in Indonesia, affecting 21.50% of the population. In the province of Bali, the stunting rate is 14.4%. The highest incidence of stunting in Buleleng is found in Banjar District, at 9.15%, primarily because Banjar District has the lowest rate of exclusive breastfeeding at just 14.3%. Currently, numerous efforts are being made to prevent stunting, one of which is promoting exclusive breastfeeding; however, many mothers still do not provide exclusive breastfeeding. The cause is attributed to poor maternal mental health. The purpose of this study is to enhance the success of mothers in providing exclusive breastfeeding to their babies through positive affirmation audio innovations based on Tri Kaya Parisudha. The method employed is a mixed-method approach, utilizing qualitative assessments for media development and quantitative distribution of questionnaires across 17 villages in Banjar District, involving a total of 34 respondents with infants. Changes in breastfeeding practices were observed before and after the intervention (one group pre-posttest). Research results: The findings from the assessments conducted by three experts—namely, a mental health expert, a lactation expert, and a Hindu cultural expert—indicate several areas that require improvement, including: the absence of technical education on breastfeeding positions, the signs of adequate breastfeeding, and a lack of explicit affirmation of breastfeeding as a gift from Ida Sang Hyang Widhi. The results of the Wilcoxon test revealed a significance value of 0.000 < 0.05, leading to the conclusion that the alternative hypothesis (Ha) is accepted. This indicates a significant influence on mental health, knowledge, attitudes, behaviors, and milk production before and after the implementation of positive affirmations for exclusive breastfeeding based on Tri Kaya Parisudha